Outcome Prediction of Neonatal Hypoxic-Ischemic Encephalopathy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Data for 205 neonates from the multicenter National Institute of Child Health trial of hypothermia in hypoxic-ischemic encephalopathy (HIE) were analyzed by using clinical and laboratory variables obtained in the NICUs within 6 hours of birth, with death or moderate/severe disability at 18-22 months or death as the outcomes.